Rethinking Institutional Identity in Religion-Based Schools: Policy Challenges from MDTA Jambi - Imran Rosyadi; Zulkipli Lessy; Muqowim Muqowim (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study examines the absence of institutional vision and policy in Madrasah Diniyah Takmiliyah Awaliyah (MDTA) in Jambi and analyzes its implications for institutional sustainability. This topic is important because MDTA operates under flexible and general regulations, making internal vision and policy crucial for ensuring organizational direction and long-term viability. The research aims to identify the factors contributing to the lack of vision and policy formulation and to assess their impact on the sustainability of MDTA institutions. Using a qualitative research design, data were collected through direct observation, in-depth interviews with the principals of Madrasah Misbahussadah and Madrasah Raudatul Islamiyah in Jambi, and a document analysis of MDTA regulations issued by the Ministry of Religious Affairs, as well as relevant literature. Data were analyzed using thematic analysis. The study reveals three main findings. First, MDTA principals lack a comprehensive and formally documented institutional vision, while policies are largely based on personal experience rather than systematic planning. Second, the absence of vision is driven by limited awareness of its strategic importance, inadequate institutional resources and support, and the lack of training in vision and policy formulation. Third, this condition results in weak institutional direction, reduced attractiveness for qualified teachers, uncertainty in decision-making, and challenges to institutional sustainability. The study emphasizes the significance of structured vision development and policy-making in enhancing MDTA governance. Future research is encouraged to explore capacity-building models and policy interventions to support the sustainable management of religion-based educational institutions in Indonesia.